High‐resolution anorectal manometry: A comparison of solid‐state and water‐perfused catheters. Issue 11 (22nd June 2017) - Rasijeff, A. M. P.; Withers, M.; Burke, J. M.; Jackson, W.; Scott, S. M.
Abstract: Background: Anorectal manometry is the most commonly performed investigation for assessment of anorectal dysfunction. Findings from previous studies comparing water‐perfused (WP) and solid‐state (SS) techniques in the anorectum are conflicting. We compared anal sphincter pressure at rest and during dynamic maneuvers (squeezing and coughing) in healthy volunteers using SS and WP high‐resolution anorectal manometry (HR‐ARM) employing equivalent catheter configurations, a standardized protocol, and identical data acquisition and analysis software. Methods: Sixty healthy volunteers (40F; median age: 40; range: 18‐74) underwent WP and SS HR‐ARM in randomized order. Anal resting pressure, and squeeze and cough increments were measured. Median pressure and 5th and 95th percentiles were calculated for each maneuver and compared using Wilcoxon signed‐rank test. Bland and Altman plots were used to assess agreement between the systems. The impact of gender and parity was also explored. Key Results: Anal sphincter pressure measurements during squeeze ( P <.001) and cough ( P <.001) were significantly higher using SS HR‐ARM than WP HR‐ARM. No differences were seen at rest between the two types of catheter (nulliparous: P =.304; parous: P =.390; males: P =.167). Normal ranges for SS and WP manometry from this small group of healthy volunteers are presented. Conclusions & Inferences: Greater sensitivity to rapid pressure change is one of the advantages associated with SS HR‐ARM. This is reflected in the differences observed during dynamic maneuvers performed during this study. Catheter type should be taken into consideration when selecting normal ranges for comparison to disease states. Abstract : Anorectal manometry is commonly used to investigate anorectal dysfunction and tests may be performed using water‐perfused or solid‐state catheters. This study assessed the agreement between the two methods using high‐resolution anorectal manometry (HR‐ARM). Solid‐state measurements of squeeze and cough pressures were found to be higher compared to water‐perfused HR‐ARM supporting the notion that interpretation of pressure measurements against normal ranges should consider the catheter‐type used to acquire pressures.